Intravitreal Bevacizumab In Diabetic Macular Edema At RSUP Cipto Mangunkusumo in 2017 - Andi Arus Victor; Masniah Masniah; Ari Djatikusumo; Elvioza Elvioza; Gitalisa Andayani Adriono; Anggun Rama Yudantha; Mario Marbungaran Hutapea (International Journal of Retina, 2019)
Introduction: Diabetic Macular Edema (DME) is a manifestation of diabetic retinopathy and is the most common cause of vision loss in diabetics. The incidence of DME has a tendency to increase, concomitant with the prevalence of diabetes globally by more than 50% from 2000 to 2030. This study aims to evaluate the proportion of central macular thickness (CMT) improvement and visual acuity in DME patients treated with intravitreal bevacizumab (IVB) injection. Methods: This study is a retrospective descriptive study. The study was conducted in the Department of Ophthalmology at RSUP Cipto Mangunkusumo (RSCM) Jakarta. Data were obtained from the medical records of all diabetic retinopathy patients with macular edema who were treated with IVB at RSCM Kirana Vitreoretina Polyclinic on January – December 2017. Results: Of the 44 subjects, improvement in best corrected visual acuity (BCVA) occurred in 24 (54.54%) subjects at the first-month evaluation and 19 (43.18%) subjects at the third-month evaluation. CMT decreased in 37 (84.41%) subjects at the first-month evaluation and 35 (81.81%) subjects at the third-month evaluation. Conclusion: Visual acuity improvement and central macular thickness reduction 3 months after IVB injection. These results strengthen IVB injection to be an alternative to adjuvant therapy in DME. Keywords: Diabetic Macular Edema, Intravitreal Bevacizumab Injection